Delegation strategy for achieving success of transport companies in South-East Nigeria - Ndu C. Vitalis, Olayinka A. Abiodun, Arukwu C. Maureen, Anthony O. Ude,; Olamide, Ohunyeye F. (Opción, 2020)
Delegation is a process that involves assigning important tasks to subordinates, giving subordinates responsibility for decisions formally made by the manager, and increasing the amount of work-related discretion allowed to subordinates. This study, therefore, sought to explore the effect of delegation on product innovation in selected motor transport companies in south east Nigeria. Cross sectional survey research design was used for the study, the population of this study was all motor transport firms in South-East, Nigeria. The study found that there was positive relationship between delegation and product innovation (r = .889*, p = 0.016 ˂ 0.05).